Penguatan Dimensi Kreatif Pada Profil Pelajar Pancasila (P5) Melalui Kegiatan Mewarnai - Rahma Susanti, Soneta; Ramadhani, Annisa; Sagita Putri, Wina; Fitri Setiani, Desi (Yayasan Darussalam Bengkulu, 2024)
This research aims to describe the coloring activities carried out by grade 1 teachers at State Elementary School 40, Bengkulu City in implementing the Pancasila student profile in the creative dimension. The method used in this research is a descriptive qualitative method, and the data collected for this research was through observa-tions and interviews conducted with the class 1 teacher and 3 students selected by the class 1 teacher to be in-terviewed in this research. Coloring activities are carried out in several stages starting from planning, implemen-tation and evaluation. The research findings reveal that this coloring activity can train and increase students' creativity by adjusting the colors in the images. Apart from that, coloring activities can also help students' de-velopment, express themselves, increase concentration and develop students' abilities. Based on the research results obtained, it is recommended for school principals to be able to facilitate SBdP learning in the P5 project, so that it can continue to be implemented, so that students can develop their creativity in strengthening the creative dimension, and for class teachers to be more creative and innovative in creating P5 projects, especially in coloring.